SENYAWA ANTIBAKTERI BIS (2-ETILHEKSIL) ESTER DAN TRITERPENOID DALAM EKSTRAK n-HEKSANA DAUN TEMPUYUNG (Sonchus arvensis L.) - I Made Sukadana; Sri Rahayu Santi (Majalah Obat Tradisional, 2011)
Isolation of antibacterial compounds from n-hexane extract of tempuyung leaf (Sonchus Arvensis L.) has been carried out. n-hexane extract (9,15 g) showed  antibacterial inhibition zone of 9 mm on Staphylococcus aureus and 8 mm on Escherichia coli at concentration of 1000 ppm.  Fractionation of n-hexane extract using column chromatography resulted on 5 fractions (F1, F2, F3, F4, and F5). Antibacterial test of the fractions toward Staphylococcus aureus and Escherichia coli showed that fraction F2 and F4 positive toward Staphylococcus aureus and Escherichia coli. Fraction F3 showed just positive toward Escherichia coli while fraction F5 just positive toward Staphylococcus aureus. Further separation using preparative thin layer chromatography (TLC) technical resulted in 3 fractions (F4.1, F4.2 and F4.3 fractions), in which F4.1 fraction indicates the most active inhibition growth test again bacterial with diametric inhibition zone of 9 mm towards Staphylococcus aureus and 11 mm for Escherichia coli within concentration of 100 ppm.   Gas Chromatography–Mass Spectroscopy (GC-MS) was employed in order to identity the F4.1 fraction. From WILEY7 database, it was identified  that isolate are mixture  of 2  compound components namely bis (2-ethylhexyl) ester and possibility of new compound included triterpenoid group  with molecule formula C32H66O6.